2001
DOI: 10.21608/jappmu.2001.258151
|View full text |Cite
|
Sign up to set email alerts
|

Fluence of Some Nitrogen Sources on Fermentation and Digestion of Different Poor Quality Roughages. 1. The Dry Matter, Neutral Detergent Fiber and Acid Detergent Fiber Disappearance of Low Quality Roughages and Some Rumen Parameters in Sheep.

Abstract: Three mature male ruminally canulated sheep were fed at 90% of their ad libitum intake. The three control rations, one from each tested roughage were formulated along with concentrate feed mixture CFM at the commonly practiced ratio being: 30% rice straw RS + 70 CFM 30% maize stalks MS + 70 CFM 40% clover straw CS + 60 CFM With the objective of increasing the use of roughage, six tested diets were formulated two from each roughage by almost doubling their ratio as in the respective control diets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was surprising to record that the TDN of the diet containing CFM+U was even slightly higher than the control despite the small improvement in the fermentable NDF and the appreciable reduction in the fermentable ADF. However, it was observed that the rate of ADF disappearance of such diet was much faster than when CFM+SBM was used allowing faster cell wall breakdown and possibly longer retention time in the rumen (Nandra et al, 1993), which might partly explain the slight improvement in the TDN value (see Mehrez et al, 2001).…”
Section: Willms Et Almentioning
confidence: 99%
“…It was surprising to record that the TDN of the diet containing CFM+U was even slightly higher than the control despite the small improvement in the fermentable NDF and the appreciable reduction in the fermentable ADF. However, it was observed that the rate of ADF disappearance of such diet was much faster than when CFM+SBM was used allowing faster cell wall breakdown and possibly longer retention time in the rumen (Nandra et al, 1993), which might partly explain the slight improvement in the TDN value (see Mehrez et al, 2001).…”
Section: Willms Et Almentioning
confidence: 99%